Gut Microbiota Associated With Effectiveness And Responsiveness to Mindfulness-Based Cognitive Therapy in Improving Trait Anxiety - Wang, Zonghua; Liu, Shuang; Xu, Xiaoxiao; Xiao, Yufeng; Yang, Min; Zhao, Xiaoyan; Jin, Cancan; Hu, Feng; Yang, Shiming; Tang, Bo; Song, Caiping; Wang, Tao (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The mindfulness based interventions have been widely demonstrated effective on reducing stress, alleviating mood disorders and improving quality of life; however, the underlying mechanisms remained to be fully understood. Along with the advanced research in microbiota-gut-brain axis, this study aimed to explore the impact of gut microbiota on the effectiveness and responsiveness to mindfulness-based cognitive therapy (MBCT) among high trait anxiety populations. Design A standard mindfulness-based cognitive therapy (MBCT) was performed among 21 young adults with high trait anxiety. A total of 29 healthy controls were matched for age and sex. The differences on gut microbiota between the two groups were compared. The changes of fecal microbiota and psychological indicators were also investigated before and after the intervention. Results Compared with healthy controls, we found markedly decreased bacterial diversity and distinctive clusters among high trait-anxiety populations, with significant overgrowth of bacteria such as Streptococcus, Blautia, Romboutsia, and decrease of genera such as Faecalibacterium, Coprococcus_3, Lachnoclostridium. Moreover, MBCT attenuated trait-anxiety and depression, improved mindfulness and resilience, and turned gut microbiota more close to that of healthy controls. Notably, high burden of intestinal Subdoligranulum pre-MBCT was associated with an increased responsiveness to MBCT. Decreases in Subdoligranulum post-MBCT were indicative of ameliorated trait anxiety. The tryptophan metabolism pathways were significantly over-represented among high-responders compared to low-responders. Conclusion The significantly increased diversity post-MBCT added evidence to gut-brain communication, and highlighted the utility of mycobiota-focused strategies for promoting effectiveness and responsiveness of the MBCT to improve trait anxiety.